Heterogeneous biomass combined cycle gasification for energy generation in Northern Mindanao a plant design - Esparcia, Eugene Jr; Lee, Kimberly Trix; Sy, Wenchester Charlson
This study aims to investigate the feasibility of a biomass combined cycle gasification power plant in Northern Mindanao to supply the demand of electricity in the region. Northern Mindanao has annual pineapple and corn production of more than 5 million metric tons, equivalent to almost 1 million metric tons of recoverable biomass. This translates to 85 MW of electricity based on a 68 percent total plant efficiency; most of it can be supplied to the unelectrified sitios of Mindanao. The proposed plant location is in Phividec Industrial Estate in Villanueva, Misamis Oriental because it is situated in a PEZA (Philippine Economic Zone Authority) land area which would provide additional advantages such as tax credits, government assistance, and possible funding. A chapter on process synthesis explores the methods of converting pineapple leaves, corn cobs, and corn stalks into useful producer gases. Its goal of determining the most appropriate technology given the characteristics of the feed and the scale of power to be produced has been solved through comparison and elimination among available technologies. For the gasifier, a circulating fluidized bed has been selected primarily because of its excellent compatibility with biomass and its capacity which cover up to 100 MW. Circulating fluidized bed gasifiers also provide good mixing, temperature uniformity, and long residence time. The gasifying medium, which is steam, was also selected for the process. The cost of operation and syngas quality produced are primarily the determining factors in selecting the gasifying medium. For the economic analysis, a net present value of US Dollar 460,939,464 from a total capital investment of US Dollar 54,580,000 was calculated with a 26 percent Internal Rate of Return and a payback period of less than 4 years. Will all of these in mind, it can be concluded that establishing a biomass gasification power plant in Northern Mindanao is feasible and profitable.